Paternités cachées, paternités impensées : être père en prison - Marine Quennehen (Genre, Sexualité et Société)
Penal policies assert their intention to maintain family connections, considered as an essential condition for prisoners’ rehabilitation and prevention of recidivism. However, there are significant differences in the treatment of parenthood in prison. Paternity is moved at the periphery of the institution. It struggles to acquire a predominant position in the narratives, practices and spaces of male detention. The institution also organizes its borders by relegating paternity and more generally family connections to certain spaces (parlor and family visiting units). In contrast, maternity has a strong position in all custody, whether the spaces are specifically reserved for it or not. Based on analyses of guards’ discourse, inmates’ invisibilization strategies implemented by inmates and by comparing the treatment of parenthood according to gender, this article shows how fatherhood is invisibilized in detention.